2013
DOI: 10.5539/gjhs.v5n2p187
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infection among Symptomatic Outpatients Visiting a Tertiary Hospital Based in Midwestern Nigeria

Abstract: Microbial pathogens implicated in urinary tract infection and their antibiotic susceptibility patterns as prevalent in UTI symptomatic outpatients resident in Benin City, Nigeria was the focus of this study. One hundred (100) midstream urine samples were collected into sterile plastic universal bottles from outpatients who visited the University of Benin Teaching Hospital, Nigeria and who were tentatively diagnosed as manifesting symptoms of UTI. Patients were referred to the Medical Microbiology department by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
23
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 21 publications
10
23
6
Order By: Relevance
“…This is contrary to the findings of [1] [2], who found Klebsiella species to be more prevalent than E. coli in UTIs. However, the result compares favourably with the findings of other workers [2] [8] [11] [30]- [34] who found E. coli more predominant over Klebsiella species.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…This is contrary to the findings of [1] [2], who found Klebsiella species to be more prevalent than E. coli in UTIs. However, the result compares favourably with the findings of other workers [2] [8] [11] [30]- [34] who found E. coli more predominant over Klebsiella species.…”
Section: Discussioncontrasting
confidence: 56%
“…[19] recorded a much lower rate of 11.9% while [20], had a high rate of 25.6%. However, it is important to note that much higher prevalence rates have been reported by some authors [1] [9] [21]- [24], with a range of 39.0% -71.6%.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Several reports are available on the mechanism of quinolone resistance in either E.coli or K.pneumoniae or even both or quinolone resistance in ESBL producing bacteria; however, no report is available on the actual resistance of nalidixic acid and ciprofloxacin in these two isolates [29][30][31][32][33][34][35] , except few published studies on urinary isolates, [36][37][38][39][40] whereby low prevalence has been reported as compared to our study. Study performed in our neighboring country reported 17% and 38% of E. coli isolates obtained from uncomplicated and complicated UTI respectively, were found resistant to ciprofloxacin.…”
Section: Quinolone Esbl Resistance and Integronscontrasting
confidence: 49%